A review of assessment indicators used by Healthy Municipalities and Communities Program in Latin America and the Caribbean region. (13th July 2019) - Chaparro, Raul; Melendi, Santiago; Santero, Marilina; Seijo, Mariana; Elorriaga, Natalia; Belizan, Maria; Rubinstein, Adolfo; Irazola, Vilma
Abstract: The Healthy Municipalities and Communities Strategy (HMCS) was developed by the Pan American Health Organization in 1990. Evaluation and monitoring are fundamental components of health promotion policies. The aim of this study is to explore the indicators used in Latin America and the Caribbean (LAC) countries to assess the performance of HMCS. We searched MEDLINE, EMBASE, LILACS, BVSDE and Google Advanced Search for documents published between January 2000 and April 2016. We included only documents with assessment indicators of the strategy. All articles were independently assessed for eligibility by pairs of reviewers. We classified the indicators with a supporting framework proposed by O'Neill and Simard (Choosing indicators to evaluate Healthy Cities projects: a political task? Health Promot Int 2006, 21, 145–152.). Local level indicators figured far more prominently among countries and were distributed both in projects and specific activities. Regarding the evolution of the HMCS, indicators were reported in the five levels of analysis (local projects and activities, provincial, national and international networks). Empowerment was represented through the presence of active community organizations and different methods of community participation (forums, open hearing and participation maps). Public policies (such as for tobacco cessation) and bylaws adherence and changes in school's curricula regarding healthy eating were frequently mentioned. However, this review demonstrated that impact indicators related to lifestyle changes or built environment are not clearly defined and there is a lack of indicators to measure progress in achieving change in long-term outcomes in LAC. We highlight the importance of designing validated indicators for measuring the impact of health promotion policies in partnership with each country involved.